BIOSYNTHESIS AND DYNAMICS OF ACCUMULATION OF SESQUITERPENE LACTONES IN ARTEMISIA GLABELLA KAR. ET KIR. - Mantler S.N.,; Zhakanov M.M.,; Adekenov S.M., (Academic Scientific Journal of Chemistry, 2020)
The study of biosynthetic processes in plant cells and methods for their regulation is an important aspect in the development of biotechnological methods for the production of valuable medicinal compounds. The identification and establishment of enzyme structures involved in the formation of secondary metabolites in plants by using molecular genetic methods is one of the relevant ways in the study of their biosynthesis. For a successful search, it is necessary to use plant organs with their quantitative accumulation. In this work for the first time, a quantitative assessment of the content of sesquiterpene lactones arglabin and argolide in CO2-extracts of Artemisia glabella Kar. et Kir. individual organs were performed at different stages of the growing period (start of regrowth, end of regrowth, budding, flowering, fruiting); using electron scanning microscopy, the leaves surface morphology was determined. It was found that the quantitative accumulation of arglabin is observed during budding stage and its amounts are 1.90% in leaves and 1.56% in buds. On the surface of leaves Artemisia glabella Kar. et Kir., there are capitate glandular trichomes of an oval shape, the sizes of which vary between 70-80 microns in length and 33-38 microns in width. Based on the obtained experimental data, we assume that the leaves and buds of intact plant Artemisia glabella Kar. et Kir. during the budding stage will be the optimal samples to search for genes involved in the biosynthesis of sesquiterpene lactones.